Effects of Y₂O₃, Pd and Rh₂O₃ Added in TiO₂ based Sensors Materials - M.Z.A, Malek; Zarina K.A, Ku; Adilah, Nor; A, Isnin (Malaysian Journal of Science, 2002)
X-ray diffractometry and conductivity data are used to establish the understanding of phase transformation in titania-based sensor materials. Phase identification of titania in the anatase phase to rutile phase was carried out by X-ray diffractometry. The X-ray diffractometry and conductivity test of titania-based was carried-out at room temperature. The anatase structure of titania-based materials was found modified when it was mixed with yttria, palladium and rhodium (III) oxide. It was observed that yttria increased the transformation of anatase to rutile phase. However, the presence of palladium and rhodium (III) oxide in titania-yttria modification had slowed down the transformation of anatase to rutile. The presence of anatase phase increased the conductivity while the rutile phase apparently inhibited the conductivity in the titania-based and titania modified based materials.